Systemic effects of acute cigarette smoke exposure in mice. (July 2014) - Itoh, Masayuki; Tsuji, Takao; Nakamura, Hiroyuki; Yamaguchi, Kazuhiro; Fuchikami, Jun-ichi; Takahashi, Maki; Morozumi, Yoshitomo; Aoshiba, Kazutetsu
Abstract Context: Cigarette smoke (CS) causes both pulmonary and extrapulmonary disorders. Objective: To determine the pulmonary and extrapulmonary effects of acute CS exposure in regard to inflammation, oxidative stress and DNA damage. Materials and methods: Mice were exposed to CS for 10 days and then their lungs, heart, liver, pancreas, kidneys, gastrocnemius muscle and subcutaneous (inguinal and flank) and visceral (retroperitoneum and periuterus) adipose tissues were excised. Bronchoalveolar lavage fluid samples were obtained for differential cell analysis. Inflammatory cell infiltration of the tissues was assessed by immunohistochemistry for Mac-3+ cells, F4/80+ cells and CD45+ cells. Oxidative stress was determined by immunohistochemistry for thymidine glycol (a marker of DNA peroxidation) and 4-hydroxy hexenal (a marker of lipid peroxidation), by enzyme-linked immunosorbent assay for protein carbonyls (a marker of protein peroxidation) and by measurements of enzyme activities of glutathione peroxidase, superoxide dismutase and catalase. DNA double-strand breaks were assessed by immunohistochemistry for γH2AX. Results: CS exposure-induced inflammatory cell infiltration, oxidative stress and DNA damage in the lung. Neither inflammatory cell infiltration nor DNA damage was observed in any extrapulmonary organs. However, oxidative stress was increased in the heart and inguinal adipose tissue. Discussions: Induction of inflammatory cell infiltration and DNA damage by acute CS exposure was confined to the lung. However, an increased oxidative burden occurred in the heart and some adipose tissue, as well as in the lung. Conclusions: Although extrapulmonary effects of CS are relatively modest compared with the pulmonary effects, some extrapulmonary organs are vulnerable to CS-induced oxidative stress.